Model Protective Films on Cu-Zn Alloys Simulating the Inner Surfaces of Historical Brass Wind Instruments by EIS and XPS - Fantauzzi, Marzia; Elsener, Bernhard; Cocco, Federica; Passiu, Cristiana; Rossi, Antonella (Frontiers in Chemistry, 2020)
The present work focuses on the characterization of brass surfaces after contact with artificial saliva solution at pH 7.4 and phosphate buffer solution at pH 7 simulating two extreme conditions that might occur when playing ancient brass wind instruments in the context of historically informed performance practice. The composition and the morphology of the film formed following the contact with the solutions for 1, 3, and 16 h were investigated by ex situ X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) to shed a light on the surface changes upon time. In situ electrochemical impedance spectroscopy (EIS) was used to study the mechanism of corrosion and protection of the alloys. The results could be interpreted using a reliable equivalent electrical circuit; they provided evidence that the alloys behave differently when in contact to the various solutions. In saliva solution the formation on the brass surface of a thick surface film was observed, composed of crystallites of about 200 nm size mainly composed of CuSCN and Zn3(PO4)2. This layer hinders the alloy dissolution. The contact of the alloys with the buffer solution originated a much thinner layer composed of Cu2O, ZnO, and a small amount of Zn3(PO4)2. This film is rapidly formed and does not evolve upon time in a protective film.